2016
DOI: 10.1002/cncr.30070
|View full text |Cite|
|
Sign up to set email alerts
|

Colorectal cancer screening: Estimated future colonoscopy need and current volume and capacity

Abstract: Background In 2014 a national campaign was launched to increase colorectal cancer (CRC) screening rates in the U.S. to 80% by 2018; it is unknown if there is sufficient colonoscopy capacity to reach this goal. We estimate the number of colonoscopies needed to screen 80% of the eligible population with fecal immunochemical testing (FIT) or colonoscopy, and if there is sufficient colonoscopy capacity to meet the need. Methods The Microsimulation Screening Analysis-colon (MISCAN-colon) model was used to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(152 citation statements)
references
References 29 publications
1
148
0
3
Order By: Relevance
“…Whereas newer CRC screening programs based on mailed fecal immunochemical tests and screening colonoscopy can reach a majority of patients in some settings [35,36], there is concern that fecal immunochemical tests may be less sensitive than colonoscopy for right-sided colorectal cancers [37]. Colonoscopy resources are also limited [38], and there is evidence of overuse of screening and surveillance colonoscopy in the USA [31,32], which may reduce access for others with higher risk of CRC. Our CRC detection model can be applied to broad populations to identify persons at increased risk of CRC (in particular, right-sided CRC); this can enable organized health systems to more effectively target colonoscopy resources.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas newer CRC screening programs based on mailed fecal immunochemical tests and screening colonoscopy can reach a majority of patients in some settings [35,36], there is concern that fecal immunochemical tests may be less sensitive than colonoscopy for right-sided colorectal cancers [37]. Colonoscopy resources are also limited [38], and there is evidence of overuse of screening and surveillance colonoscopy in the USA [31,32], which may reduce access for others with higher risk of CRC. Our CRC detection model can be applied to broad populations to identify persons at increased risk of CRC (in particular, right-sided CRC); this can enable organized health systems to more effectively target colonoscopy resources.…”
Section: Discussionmentioning
confidence: 99%
“…The ACS remains fully committed to increasing screening rates; both expanding the screening to include adults aged 45 to 49 years and increasing screening rates in the population aged 50 years and older can be achieved within the current health care infrastructure. A study that combined results from the 2012 Survey of Endoscopic Capacity with a modeling analysis indicated that increasing screening rates to 80% (with any combination of screening modalities) can be accommodated with current excess capacity . In addition, this guideline places increased emphasis on choice of screening options (not limited to colonoscopy) for those initiating CRC screening.…”
Section: Discussionmentioning
confidence: 99%
“…First, the potential harms of colonoscopy (as either a primary screening or follow‐up examination) are lower in younger versus older adults . Second, recent estimates indicate that the current colonoscopy capacity in the United States should be able to accommodate the anticipated increase in colonoscopies, performed both as primary screens and as follow‐up to positive noncolonoscopy tests . Finally, starting CRC screening earlier also may contribute to reducing disparities in population groups with a higher disease burden (including blacks, Alaska Natives, and some American Indian groups).…”
Section: Recommendationsmentioning
confidence: 99%
“…First, with respect to capacity, we noted a recent study by Joseph et al exploring whether screening capacity was sufficient to fulfill the National Colorectal Cancer Roundtable (NCCRT) goal for the nation of 80% screening by 2018. Over a period from 2014 to 2040, a colonoscopy‐only scenario would require from 11 to 13 million colonoscopies annually, with an additional capacity of up to 10.5 million colonoscopies available . Some confidence can be derived from these results; however, throughout the United States, there are areas in which a colonoscopy is not easily obtained, and large segments of the target population do not have access because they are uninsured or underinsured.…”
Section: Screening and Surveillance For The Early Detection Of Adenommentioning
confidence: 99%